A Stoichiometric Solvent-Free Protocol for Acetylation Reactions - Valentini, Francesca; Galloni, Pierluca; Brancadoro, Diana; Conte, Valeria; Sabuzi, Federica (Frontiers in Chemistry, 2022)
Considering the remarkable relevance of acetylated derivatives of phenols, alcohols, aryl and alkyl thiols in different areas of biology, as well as in synthetic organic chemistry, a sustainable solvent-free approach to perform acetylation reactions is here proposed. Acetylation reactions are classically performed using excess of acetic anhydride (Ac2O) in solvent-free conditions, or eventually working with stoichiometric amounts of Ac2O in organic solvents; both methods require the addition of basic or acid catalysts to promote the esterification. Therefore, they usually lead to the generation of high amounts of wastes, that sensibly raise the E-factor of the process. With the aim to develop a more sustainable system, a solvent-free, stoichiometric acetylation protocol is thus proposed. The naturally occurring phenol, thymol, can be converted to the corresponding - biologically active - ester with good yields, in the presence of 1% of VOSO4. Interestingly, the process can be efficiently adopted to synthesize other thymyl esters, as well as to perform acetylation of alcohols, aryl and alkyl thiols. Remarkably, a further improvement has been achieved replacing Ac2O with its greener alternative, isopropenyl acetate (IPA).